2017
DOI: 10.1093/jac/dkx374
|View full text |Cite
|
Sign up to set email alerts
|

Association between prior antibiotic therapy and subsequent risk of community-acquired infections: a systematic review

Abstract: We found an association between prior antibiotic use and subsequent risk of a diverse range of community-acquired infections. Gastrointestinal and skin and soft tissue infections were most frequently found to be associated with prior antibiotic exposure. Our findings support the hypothesis that antibiotic use may predispose to future infection risk, including infections caused by both antibiotic-resistant and non-resistant organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Given the aforementioned evidence of the role of the microbiota in systemic priming of immune responses and the extensive amount of disruption of the microbiota observed in our cohort, it is vital to investigate new treatment strategies that preserve these microorganisms during infection. For example, overuse of antibiotics and their associated transient alteration of the microbiota have implications for outcome, which was supported by a recent systematic review that found a statistically significant association between antibiotic exposure and subsequent risk of community-acquired infections [ 42 ]. In addition, our study highlights a new opportunity for the development of next-generation pre- or probiotics to enhance the abundance of obligate anaerobic bacteria as a potential adjuvant therapy during or following the treatment of TF and other infectious diseases.…”
Section: Discussionmentioning
confidence: 98%
“…Given the aforementioned evidence of the role of the microbiota in systemic priming of immune responses and the extensive amount of disruption of the microbiota observed in our cohort, it is vital to investigate new treatment strategies that preserve these microorganisms during infection. For example, overuse of antibiotics and their associated transient alteration of the microbiota have implications for outcome, which was supported by a recent systematic review that found a statistically significant association between antibiotic exposure and subsequent risk of community-acquired infections [ 42 ]. In addition, our study highlights a new opportunity for the development of next-generation pre- or probiotics to enhance the abundance of obligate anaerobic bacteria as a potential adjuvant therapy during or following the treatment of TF and other infectious diseases.…”
Section: Discussionmentioning
confidence: 98%
“…The antibiotic-mediated depletion of commensal bacteria decreases intestinal RegIII-γ expression, which normally acts to resist colonization by VRE 14 . Furthermore, these disruptions in the microbiota may predispose a patient to recurrent infection and sepsis 15 , 16 . Not surprisingly, microbiota-targeted therapies are being developed to prevent or treat sepsis 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…International travelers are at increased risk of acquiring QNS enteric bacterial infections and importing them into the United States, which can lead to onward transmission and domestic outbreaks of infections that are difficult to treat [4, 16]. Empiric antimicrobial treatment of travelers’ diarrhea is rarely required, is more common when travelers carry antibiotics with them [21], and may exacerbate the problem of acquisition and importation of antibiotic-resistant infections [3, 22, 23]. Fluroquinolones can also precipitate serious adverse events, such as rupture of the Achilles tendon, fatal dysrhythmias, and C .…”
Section: Discussionmentioning
confidence: 99%